2019
DOI: 10.4314/gjds.v16i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child level factors associated with childhood (0-23 months) diarrhoea in Ghana: a pooled analysis of national representative datasets

Abstract: In Ghana, diarrhoea is one of the leading causes of childhood morbidity and mortality. The objective of this study was to examine maternal and child level factors associated with diarrhoea among children in Ghana. A weighted group of 4,821 mother-child dyads was used for the analysis. The analysis was restricted to mothers with children under 2 years of age. Multivariate logistic regression analysis was performed on the pooled data. The pooled prevalence of diarrhoea among the children was 18 per cent. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
5
2
0
Order By: Relevance
“…The odds of developing diarrheal diseases is higher in children who were aged 7–12 and 13–24 months compared to children aged 0–6 months. This finding is in agreement with other studies [ 7 , 14 16 , 33 ]. This high odds of childhood diarrhea prevalence might attribute to the start of supplementary feeding after the age of six months.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The odds of developing diarrheal diseases is higher in children who were aged 7–12 and 13–24 months compared to children aged 0–6 months. This finding is in agreement with other studies [ 7 , 14 16 , 33 ]. This high odds of childhood diarrhea prevalence might attribute to the start of supplementary feeding after the age of six months.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, being children born from mothers belonging to low community-level educational status and being male are at high probability of experiencing diarrhea as compared to counterparts. A similar declaration was also made by other studies [ 8 , 16 , 18 , 38 , 39 ]. Lastly, children of not working mothers have a 12% lower odds to have diarrhea than those of mothers who work.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study also found that children aged 6-11 months and 12-23 months had higher odds of diarrhoea and ARI compared to their peers aged 0-5 months. This finding is consistent with many previous studies [11,[33][34][35][36]. Children within the ages of 0-5 months in Ghana are usually exclusively breastfed [8], and therefore our observed finding may be a reflection of the important role exclusive breast feeding plays in reducing diarrhoea and respiratory infection in children who are exclusively breastfed [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…This is not surprising as education helps women to be well informed on how to access and apply information on child health. This finding in our study has been reported by other studies [16,33]. We also found that children in the richest households had lower odds of diarrhoea compared to children in the poorest households.…”
Section: Discussionsupporting
confidence: 92%